2014
DOI: 10.1186/ar4579
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced neutrophil extracellular trap generation in rheumatoid arthritis: analysis of underlying signal transduction pathways and potential diagnostic utility

Abstract: IntroductionNeutrophil extracellular traps (NETs) have recently been implicated in a number of autoimmune conditions, including rheumatoid arthritis (RA). We examined the underlying signaling pathways triggering enhanced NETosis in RA and ascertained whether the products of NETosis had diagnostic implications or usefulness.MethodsNeutrophils were isolated from RA patients with active disease and from controls. Spontaneous NET formation from RA and control neutrophils was assessed in vitro with microscopy and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
306
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(323 citation statements)
references
References 36 publications
12
306
0
5
Order By: Relevance
“…We have recently observed that cfDNA concentrations were elevated in serum, but not in plasma samples, of RA patients, when compared to similar samples from matching healthy control donors [11]. By determining that the serum cfDNA consisted of nucleosome/MPO complexes, we were able to show that the vast proportion of serum cfDNA was derived from neutrophils undergoing NETosis during the clotting procedure [11].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…We have recently observed that cfDNA concentrations were elevated in serum, but not in plasma samples, of RA patients, when compared to similar samples from matching healthy control donors [11]. By determining that the serum cfDNA consisted of nucleosome/MPO complexes, we were able to show that the vast proportion of serum cfDNA was derived from neutrophils undergoing NETosis during the clotting procedure [11].…”
Section: Introductionmentioning
confidence: 88%
“…Consequently, NET-derived products can be detected by examining for complexes of cfDNA and neutrophil granular proteins [9]. Aberrant or excessive NET generation has been noted in a number of human pathologies, including PE [10], small vessel vasculitis [9], or rheumatoid arthritis (RA) [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Several of these proteins, such as histones, MPO, PR3, HMGB1 and LL37, possess proinflammatory characteristics and NETs have in vitro been shown to induce interferon (IFN)-α production in dendritic cells (5), cause epithelial and endothelial cell damage (6)(7)(8) and act as bridge between the innate and adaptive immune system (9). NETs trap and kill microbes, including bacteria, fungi and protozoa (3,(10)(11)(12)(13)(14) but have also been connected to various autoinflammatory or autoimmune diseases, such as preeclampsia, systemic lupus erythematosus (SLE), Felty´s syndrome (FS) and rheumatoid arthritis (RA) (15)(16)(17)(18)(19). NETs have also been suggested to be important in a rodent model of drug-induced vasculitis (20), implying a role of NETs in the pathogenesis of AAV as well.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that the other stimulus used by us in paper I and II, TNF and ANCA, can induce NETosis (Kessenbrock et al 2009, Keshari et al 2012), but also that NETosis can occur spontaneously in unstimulated neutrophils (Sur Chowdhury et al 2014, Tang et al 2015. Although one cannot exclude that also necrotic cells are being stained with this method, it is beneficial that no NETs are being lost during the measurements.…”
Section: Cell Death Assaymentioning
confidence: 99%
“…In addition to their role as antimicrobial agents, NETs of both nuclear and mitochondrial origin have been connected to autoinflammatory or autoimmune diseases (Gupta et al 2005, Kessenbrock et al 2009, Dwivedi et al 2012, Khandpur et al 2013, Leffler et al 2013, Sur Chowdhury et al 2014, Surmiak et al 2015, Lood et al 2016, and have therefore been referred to as a double edged sword of innate immunity (Kaplan and Radic 2012).…”
Section: Extracellular Trapsmentioning
confidence: 99%